Antibiotic prescription rationality and associated in‑patient treatment outcomes in children under‑five with severe pneumonia at Bwizibwera health center IV, Mbarara District, South‑Western Uganda - Abeja, Christine Joy; Niyonzima, Vallence; Byagamy, John Paul; Obua, Celestino (Pneumonia, 2022)
Background: Pneumonia is a major cause of morbidity and mortality in children under five. Antibiotic treatment must be started immediately in children with pneumonia. The irrational use of antibiotics may increase morbidity and mortality in children with pneumonia. Pneumonia accounted for approximately 16% of the 5.6 million under-five deaths word wide in 2016. In Uganda, it kills approximately 2,400 children per year. Early diagnosis and appropriate case management with rational use of antibiotics remain the most effective intervention to reduce pneumonia related mortality. This study aimed at determining antibiotic prescription rationality and associated in-patient treatment outcomes in children aged 2–59 months with severe community-acquired pneumonia at Bwizibwera Health Centre IV from 1st May 2018 to 30th April 2019. Methods: We conducted a retrospective cohort study design; data were collected from in-patient records of all children aged 2–59 months with severe community-acquired pneumonia who met the eligibility criteria for a period of one year. Data abstraction template was used for data collection. Health care records of children aged 2–59 months who had other co-morbidities and were on medication that could influence or impact on in-patient treatment outcomes from 1st May 2018 to 30th April 2019 were excluded. Data was entered and analyzed using Epi-info v 7.2 and STATA v 13.0 respectively, Descriptive statistics were reported and Chi-square test was used to compare the proportions. Results: Of the total records of children retrieved and screened (N = 847), 229 prescription records of children fulfilled inclusion criteria, 57 (24.9%) had rational prescriptions with good outcomes and 172 (75.1%) had irrational prescriptions with 10 (4.4%) having unfavorable outcomes. The majority (73.7%) of those who received rational prescription were on treatment with a combination of benzyl penicillin plus gentamycin while (26.3%) were on ampicillin plus gentamycin. The majority (32.4%) of patients with good treatment outcomes were aged 6 – 11 months. This age category also doubled as the group that experienced the highest percentage (40.0%) of unfavorable outcomes. There were no statistically significant associations between patient characteristics and treatment outcomes. Conclusion: In conclusion, the majority of children had irrational antibiotic prescriptions and 40 percent of children aged 6–11 Months had unfavorable treatment outcomes with 20 percent death. This study also found out that majority of antibiotic prescription among children under five was irrational and it’s against Uganda clinical guideline for treatment of severe pneumonia among children under five.
Keywords: Antibiotic; Children; Rationality; Pneumonia; Prescription; Treatment outcomes; Bwizibwera; Health center IV